Technology Progress On Photovoltaic Thermal (PVT) Systems With Flat-Plate Water Collector Designs: A Review - Abdullah, Amira Lateef; Misha, Suhaimi; Tamaldin, Noreffendy; Mohd Rosli, Mohd Afzanizam; Sachit, Fadhil Abdulameer (Penerbit Akademia Baru, 2019)
Commercial solar cells are currently less efficient in converting solar radiation into electricity. Photovoltaic (PV) performance decreases as temperature increases. Many efforts have been made to investigate and develop hybrid PV and thermal collector systems. A photovoltaic thermal (PVT) system generates both electric power and heat simultaneously. A significant amount of work has been carried out on these systems since 1970. Different PVT systems have been invented in the last 30 years. The aim of PVT systems is to improve electrical efficiency using a cooling system by reducing cell temperature, and an absorber collector takes the excess heat underneath the PV system. Then, the heat is transferred through working fluids such as water. The harvested heat is further used in low-temperature applications, including domestic hot water supply, water preheating, and space heating. This work shows the developments of the PVT systems, development of PVT systems with spectrum filters in recent research, the development and design of flat-plate water collectors in PVT systems, including various types of flat-plate solar collectors, and also a broad classification and review of published research work on the systems. The performance of PVT-based water collectors is determined by different combinations of absorption collectors and solar collectors as important elements of PVT systems. New design ideas and innovative configurations have emerged, especially when liquid as a medium of heat transfer is utilized to obtain useful heat from the back surfaces of PV panels. Various design configurations for hybrid PVT collectors are also compiled and assessed, and the emphasis is on the design performance of absorbers. The findings show that solar collector design parameters can easily affect and enhance the overall performance of PVT systems, especially electrical and thermal efficiency. The general performance of PVT systems may have benefited significantly from the extensive research conducted on this topic since the last decade. In order to develop novel PVT systems, more effort is needed in accurate modelling, exploration of novel materials, enhancement of PVT system stability, and the design of a supporting energy storage system.